Aesthetic Representation of the Character Values of Tolerance and Nationalism in Chinese-Motif Batik Lasem - Rizkyhimawan, Adhytia; Syah, Naziah Nilda; Suparti (Arty: Jurnal Seni Rupa, 2025)
This study explores the aesthetic representation of tolerance and nationalism as character values embedded in the visual elements of Chinese-motif Batik Lasem. As a cultural artifact rooted in a history of intercultural exchange, Batik Lasem reflects not only artistic beauty but also deep social and moral meanings. Using a qualitative descriptive approach, this research employs visual analysis to examine the formal elements—such as color, shape, composition, and symbolism—found in selected Chinese-influenced Batik Lasem patterns. The findings reveal that the fusion of Chinese and Javanese visual motifs embodies messages of cultural harmony, mutual respect, and national identity. The aesthetic choices made by artisans—ranging from symbolic flora and fauna to harmonious compositions—serve as a medium to communicate values of tolerance and national pride. This study contributes to the field of visual communication design by demonstrating how traditional art forms can function as effective channels for character education and interethnic understanding through visual aesthetics.